Risk Management in Reducing Audit Findings: Evidence from Indonesia Local Government - Weyha, Tifani Keren Hapuk; Furqan, Andi Chairil; Betty; Anshori, Ma'amun (Quantitative Economics and Management Studies, 2025)
Risk management has become an integral element of entity governance, particularly in the public sector, which continues to face intense scrutiny in an effort to minimize audit findings. This study aims to analyze the impact of risk management implementation on audit findings in Indonesian local governments. Through a quantitative approach and linear regression analysis in STATA-17 programming, data was obtained from local governments in 2021, with a total of 542 observations processed. The results revealed that the implementation of risk management contributed to reducing audit findings, especially those related to non-compliance with satutory regulations, including findings that resulted in local financial losses, potential financial losses, revenue shortfalls, and administrative irregularities. This study provides new insights into the important role of risk management in strengthening governance, improving accountability, and optimizing financial management in local governments. Therefore, this study underscores the importance of integrating risk management into every financial management process within local governments to minimize regulatory non-compliance and to achieve effective, efficient, and accountable financial management.